1995
DOI: 10.1002/hlca.19950780121
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 4,6,8‐Trisubstituted Methyl Azulene‐2‐carboxylates

Abstract: It is shown that sodium (methoxycarbony1)cyclopentadienide (l), which is easily accessible from sodium cyclopentadienide and dimethyl carbonate in THF, reacts with 2,4,6-trisubstituted pyrylium tetrafluoroborates Z a 4 in boiiing MeOH to afford the corresponding methyl ~izulene-2-carboxylates 4 a 4 in good yields. The corresponding 1-carboxylates 3 were not found (cf. Schemes I and 2)Whereas the synthesis of azulenes, substituted at the seven-membered ring, can easily be accomplished by the reaction of 2,4,6-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
3

Year Published

1995
1995
2012
2012

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 9 publications
0
20
0
3
Order By: Relevance
“…82 (1999) 2280 6 ) We found this effect also with other azulenes and ADM (cf. [14] , respectively. The thermal rearrangement of 2a to 9a at 1008 is twice as fast as that of 2c to 9c (vide supra).…”
Section: Formation Ofmentioning
confidence: 95%
See 1 more Smart Citation
“…82 (1999) 2280 6 ) We found this effect also with other azulenes and ADM (cf. [14] , respectively. The thermal rearrangement of 2a to 9a at 1008 is twice as fast as that of 2c to 9c (vide supra).…”
Section: Formation Ofmentioning
confidence: 95%
“…The main reaction path is determined with high periselectivity by the HOMO(azulene) and LUMO(acetylenedicarboxylate) interaction that leads to the reversible formation of the primary intermediates of type 2a (27a) in a [4 2] manner. Other pericyclic processes do not play a significant role despite the fact that they result in the formation of products of type 12a (29a) or intermediates such as 13a (25a) which display much larger DH 0 f differences with respect to the reactants (1(24) ADM ) 14 E Me groups of the acetylene unit cause significant differences in the DDH 0 f values 14 ). Fig.…”
Section: Tricyclic Compounds Of Type 12mentioning
confidence: 97%
“…IR (film): 3068w, 3000m, 2951s, 2844w, 1738vs, 1725vs, 1635s, 1484m, 1 4 3 6~ 1365~1, 1250vs, 1197vs, 1152vs, 1069w, 987~1, 900m, 836w, 770.7, 659vw, 604vw1, 489vw. 346 (18, [M(ll) + NH,]+), 333 (18), 332 (100, [M(DME) + NH,]+), 329 (7, [M(11) + HI+), 316 (6), 315 (27, [M(DME) + HI'), 300 (16), 283 (24), 282 (7).…”
Section: 32mentioning
confidence: 97%
“…[5]. The reaction is also applicable to benz [a]azulene (31) itself and dimethyl acetylenedicarboxylate (ADM) [7] (see also [6]) and opens an easy access to 30 particularly, in view of a new synthesis of 31 that has been developed by us [22] (see also [23] showed that the thermal reaction in aromatic hydrocarbons such as toluene gave the best yields of the benzo[a]heptalenedicarboxylates with a minimum number of by-products (see also [8] [24] [23]), since heptafulvene shows exactly this type of periselectivity in cycloaddition reactions (cf. [25]).…”
Section: D23bmentioning
confidence: 99%
“…We thus have prepared the corresponding anion, lithium carbomethoxycyclopentadienide (4), by treatment of cyclopentadiene with sodium hydride in THF, followed by addition of dimethyl carbonate [35]. We thus have prepared the corresponding anion, lithium carbomethoxycyclopentadienide (4), by treatment of cyclopentadiene with sodium hydride in THF, followed by addition of dimethyl carbonate [35].…”
Section: Chemistry Of Dimerizationmentioning
confidence: 99%